The effect of a Schema-based method on correcting persistent errors in mental arithmetic: an experimental study - Chen, Shufang; Liu, Dawei; Yan, Huifen; Ma, Yong (Frontiers in Psychology, 2024)
Arithmetic calculation is a fundamental skill for mathematical learning and daily life. However, elementary school students often make errors in practice.Grounded in the schema theory and the memory retrieval theory of mental arithmetic, this study employs a controlled experiment to investigate the effect of a schema-based method in correcting persistent errors in mental arithmetic, specifically in the context of simple addition operations. The experimental group utilizes a schema-based method to help participants rectify incorrect answers in memory retrieval, while the control group did not receive this treatment. The results showed that significant differences emerged between the experimental and control groups in both the post-test performance and the reduction of persistent error count, indicating that the experimental group had rectified incorrect answers in memory; and persistent errors in simple addition were indeed caused by interference from incorrect answers during memory retrieval; and the schema-based method proves to be effective. The findings of this study contribute to enhancing practical mental arithmetic instruction, assisting students in correcting relevant errors, and improving their mental arithmetic abilities.Not only does it offer directive guidance for teaching practices, but it also provides an enlightening reference for promoting innovative teaching methods.